Transversus abdominis plane block with liposomal bupivacaine compared to oral opioids alone for acute postoperative pain after laparoscopic hysterectomy for early endometrial cancer: a cost-effectiveness analysis - Seagle, Brandon-Luke L. (Gynecol Oncol Res Pract, 2017)
BACKGROUND: To determine the cost-effectiveness of transversus abdominis plane block with liposomal bupivacaine (TAP) compared to oral opioids alone for acute postoperative pain after laparoscopic hysterectomy for early endometrial cancer. METHODS: A cost-effectiveness analysis using a decision tree structure with a 30.5 day time-horizon was used to calculate incremental cost-effectiveness ratio (ICER) values per quality-adjusted life-year (QALY). Base-case costs, probabilities, and QALY values were identified from recently published all-payer national database studies, 2017 Medicare fee-schedules, randomized trials, institutional case series, or assumed, when published values were not available. One-way, two-way and multiple probabilistic sensitivity analyses were performed. RESULTS: The TAP strategy dominated the oral opioid-only strategy, with decreased costs and increased effectiveness. Specifically, the TAP strategy saved $235.90 under the base-case assumptions. Threshold analyses demonstrated that if the relative same-day discharge probability was ≥ 12% higher in the TAP group, then TAP was cost-saving over oral opioids-alone. Similarly, TAP was cost-saving whenever the costs saved by same-day discharge compared to admission were ≥ $1115.22. Cost-effectiveness of the TAP strategy was highly robust of a variety of sensitivity analyses. CONCLUSIONS: TAP with liposomal bupivacaine was robustly cost-effective at conventional willingness-to-pay thresholds. Further, TAP was cost-saving compared to opioids-only when the same-day discharge rate among TAP users was greater than among opioid-only users. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s40661-017-0048-7) contains supplementary material, which is available to authorized users.